Pengaruh Lingkungan Belajar dan Motivasi Belajar Terhadap Hasil Belajar Siswa pada Mata Pelajaran Ekonomi: The Effect of Learning Environment and Learning Motivation on Student Learning Outcomes in Economics Subjects - Rahman, Nurilmi; Supatminingsih, Tuti; Ahmad, Muh Ihsan Said (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
This study aims to analyze the effect of learning environment and learning motivation on student learning outcomes in Economics subjects. This study uses a quantitative approach with a survey method, and a sample consisting of 61 students spread across grades X, XI, and XII. Data were collected through questionnaires that measured learning environment variables, learning motivation, and student learning outcomes. The results showed that the learning environment has a significant positive influence on student learning outcomes, which includes family, school, and community environmental factors. In addition, learning motivation, both intrinsic and extrinsic, also has a positive effect on student learning outcomes. The coefficient of determination (R²) of 0.713 indicates that the two variables are able to explain 71.3% of the variation in student learning outcomes. This study also found that the simultaneous effect of learning environment and learning motivation on student learning outcomes was highly significant, with an Fcount of 76.512 and p-value <0.05. Therefore, this study suggests that schools and families work together to create a conducive learning environment and increase student motivation in learning.